Top 10 World - Chu Ban She (Dorlind Kindersley Limited, 2012)
DK's bestselling city guides have been giving you the Top 10ofyourfavourite destinations for years. Here, they've goneonebetter,with the DK Top 10 World - a comprehensive full-colourgiftbookthat showcases the Top 10 of everything around theglobe.Divided byregion, there are themed lists for eachdestination,includingCulture amp; Tradition, Natural Wonders,Festivalsand Momentsin History. Perfect for inspiration andarmchairtravellerseverywhere, the guide takes you from the AlgarvetoAuckland andfrom Iceland to Israel, with the Top 10 foreachdestination. Thereare also listings showcasing our pick of theTop10 restaurants,markets, Bamp;Bs, hostels, hotels, spas andshopsfor eachregion. "The DK Top 10 World" truly is your guide tothe Top10 bestof everything